Studi Kritis Filsafat Ketuhanan Dalam Risalah Hayy Bin Yaqzhan Karya Ibnu Thufail - Fahmi, Zainal Fahmi (Mazalat: Jurnal Pemikiran Islam, 2025)
During the Islamic Golden Age, many great thinkers emerged, one of whom was Ibn Tufail. He is recognized as one of the leading plulosophers of the medieval period. His thoughts are reflected in his work titled "Havy Ibn Yaqzhan," where he expresses his philosophical views on the uruverse. God, religion, morality, human nature, and the culture of formal society. He attempts to explain humanity's ability to live independently, without relving on existing language, religion, culture, or traditions, which indicates that these factors do not always influence the development of human intellect. In the novel "Hayy Ibn Yaqzhan," Ibn Tufail also seeks to prove the thesis of the uruty between rational and mystical wisdom, demonstrating that humans, despite their weaknesses, can communicate with God through the power of reason (philosophy) as well as the power of the heart (Sufism).